2003
DOI: 10.1525/aa.2003.105.1.116
|View full text |Cite
|
Sign up to set email alerts
|

"Race"—Still an Issue for Physical Anthropology? Results of Polish Studies Seen in the Light of the U.S. Findings

Abstract: The racial paradigm, which became rooted in physical anthropology at its very beginning, was, for decades, treated as a concept needing no verification. It was only in the mid-20th century that the first attempts were made to question the usefulness of the race concept in describing our species variation. Since then, an ever growing number of anthropologists, particularly in the United States, have rejected the concept (nearly seventy percent in 1999). In Poland, the situation is different-in the 2001 study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Participants were asked two questions. The phrases were similar to those previously used in the U.S. and Polish studies (e.g., Lieberman et al 1989; Lieberman and Reynolds 1996; Kaszycka and Štrkalj 2002; Kaszycka and Strzałko 2003a, 2003b):…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants were asked two questions. The phrases were similar to those previously used in the U.S. and Polish studies (e.g., Lieberman et al 1989; Lieberman and Reynolds 1996; Kaszycka and Štrkalj 2002; Kaszycka and Strzałko 2003a, 2003b):…”
Section: Methodsmentioning
confidence: 99%
“…In addition, over the following few weeks, almost 300 additional persons (members of the European Anthropological Association) were asked to complete the questionnaire via e‐mail. The Polish members of the association were excluded from the third survey so as to avoid overrepresentation of anthropologists from a single country (Polish physical anthropologists had previously been comprehensively surveyed; see Kaszycka and Štrkalj 2002; Kaszycka and Strzałko 2003a, 2003b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distaste for race appears to be confined to Western anthropologists, however. A study of Polish physical anthropologists found that 75 percent of them agreed that human races are a reality (Kaszycka and Strzalko, ). The concept also appears alive and well among Chinese anthropologists.…”
Section: The Aaa Statement and Lewontin's Fallacymentioning
confidence: 99%